2017
DOI: 10.1002/ecs2.1887
|View full text |Cite
|
Sign up to set email alerts
|

Open access increases citations of papers in ecology

Abstract: Abstract. Open access (OA) can effectively increase the accessibility and visibility of scientific articles and thus potentially confer them with citation advantages. Such an impact may be more pronounced in developing countries where the cost for journal subscription is comparably expensive and usually unaffordable. By comparing one OA article with one non-OA article published in the same issue, we tested the impact of OA on citation advantages of articles published in 46 ecology journals indexed in the Journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
2
36
1
2
Order By: Relevance
“…The complexity of the debate around open access also stems from the presence of clashing stakeholder interests, where the vision for the path forward is not uniform and key actors have their own considerations and arguments for how the future of scholarly publishing should be shaped. The case for open access is sometimes based on pragmatic grounds and pointing to the increased citations that research outputs being made freely available through the web have been found to receive (Tang et al 2017;Sotudeh et al 2015;Fukuzawa 2017), though some have also argued that the positive effect on citations does not occur in all fields (Wray 2016). However, there is also an evident ethical dimension in this debate (Piccininni 1997;van Krevelen 2005;Troll Covey 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the debate around open access also stems from the presence of clashing stakeholder interests, where the vision for the path forward is not uniform and key actors have their own considerations and arguments for how the future of scholarly publishing should be shaped. The case for open access is sometimes based on pragmatic grounds and pointing to the increased citations that research outputs being made freely available through the web have been found to receive (Tang et al 2017;Sotudeh et al 2015;Fukuzawa 2017), though some have also argued that the positive effect on citations does not occur in all fields (Wray 2016). However, there is also an evident ethical dimension in this debate (Piccininni 1997;van Krevelen 2005;Troll Covey 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on OA impact and quality indicate that whether an article is published OA or not is not a reliable indicator of its quality, nor is the journal in which it is published (Bjork & Solomon, 2012;Harnad & Brody, 2004;Tang, Bever, & Yu, 2017). Studies on OA impact and quality indicate that whether an article is published OA or not is not a reliable indicator of its quality, nor is the journal in which it is published (Bjork & Solomon, 2012;Harnad & Brody, 2004;Tang, Bever, & Yu, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Responsible use of research funds requires that research findings remain accessible. Open access papers are discoverable and accessible to everyone; some evidence suggests that open access research has a higher readership (Tang et al 2017). It is too early to know if there will eventually be a tipping point whereby all papers move towards open access (beyond university repositories; see Bankier and Perciali (2008) 2018and Lehtomäki et al (2018)) and the funder or university would cover publication fees.…”
Section: Open Accessmentioning
confidence: 99%